2019
DOI: 10.1111/ejn.14327
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity for mid‐level properties of faces and places in the fusiform face area and parahippocampal place area

Abstract: Regions in the ventral visual pathway, such as the fusiform face area (FFA) and parahippocampal place area (PPA) are selective for images from specific object categories. Yet images from different object categories differ in their image properties. To investigate how these image properties are represented in the FFA and PPA, we compared neural responses to locally‐SCRAMBLED images (in which mid‐level, spatial properties are preserved) and globally‐SCRAMBLED images (in which mid‐level, spatial properties are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…While gist statistics predict category-selective responses in the occipitotemporal cortex ( Rice et al, 2014 ; Watson et al, 2014 ; Coggan et al, 2016 , 2019 ), our univariate and multivariate analysis results show that minimizing differences in gist statistics that covary with category membership do not eliminate category-selective effects. Specifically, in the ROIs that were defined separately using images of animals and tools with naturally varied gist statistics, univariate analyses conducted in the ROIs revealed stronger activations for animals than tools in the animal-selective bilateral LOC and lateral fusiform gyri, and stronger activations for tools than animals in the tool-selective left pMTG and medial fusiform gyrus for images of animals and tools with comparable gist statistics.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…While gist statistics predict category-selective responses in the occipitotemporal cortex ( Rice et al, 2014 ; Watson et al, 2014 ; Coggan et al, 2016 , 2019 ), our univariate and multivariate analysis results show that minimizing differences in gist statistics that covary with category membership do not eliminate category-selective effects. Specifically, in the ROIs that were defined separately using images of animals and tools with naturally varied gist statistics, univariate analyses conducted in the ROIs revealed stronger activations for animals than tools in the animal-selective bilateral LOC and lateral fusiform gyri, and stronger activations for tools than animals in the tool-selective left pMTG and medial fusiform gyrus for images of animals and tools with comparable gist statistics.…”
Section: Discussioncontrasting
confidence: 54%
“…Comparison of the lateral versus the medial occipitotemporal cortex shows sensitivity not only to animals versus tools, but also to curvilinear versus rectilinear shapes ( Op de Beeck et al, 2008 ; Srihasam et al, 2014 ), and low spatial frequency (LSF) versus high spatial frequency (HSF; Rajimehr et al, 2011 ; Mahon et al, 2013 ; Canário et al, 2016 ; but see Berman et al, 2017 ). Moreover, differences in image gist statistics across categories can account for category-selective response patterns in the occipitotemporal cortex ( Rice et al, 2014 ; Watson et al, 2014 ; Coggan et al, 2016 , 2019 ). Therefore, it is often difficult to tease apart the extent that visual or conceptual features associated with a category contribute to category-selective responses.…”
Section: Introductionmentioning
confidence: 99%
“…faces in its fusiform face area, FFA). Several experimental studies (Kanwisher, 2010, Coggan, Baker, & Andrews, 2019, Baldauf & Desimone, 2014DeVries & Baldauf, 2019) have shown that parts of the FFC follow relatively slow fluctuations (~2 Hz) during rhythmic face presentation and that this response was enhanced when participants attended to the face presentation. Our results suggest that the FFC (and its neighbors) allow tracking of temporally slow fluctuations in visual objects more generally.…”
Section: Attention Modulates Coherence In All Quasi-rhythmic Stimulatmentioning
confidence: 99%
“…One possibility is that the patterns of response in high-level visual areas reflect an underlying representation that is based on more fundamental properties of the stimulus (Andrews, Watson, Rice, & Hartley, 2015). Neuroimaging studies have also shown that differences in the visual properties of objects can explain a significant amount of the variance in high-level regions of visual cortex (Coggan et al, 2019;Levy et al, 2001;Rice et al, 2014;Nasr et al, 2014;Sormaz et al, 2016). However, the sparse nature of these recordings makes it difficult to determine with certainty the critical dimensions along which information is represented.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sparse nature of these recordings makes it difficult to determine with certainty the critical dimensions along which information is represented. Neuroimaging studies have also shown that differences in the visual properties of objects can explain a significant amount of the variance in high-level regions of visual cortex (Coggan et al, 2019;Levy et al, 2001;Rice et al, 2014;Nasr et al, 2014;Sormaz et al, 2016). For example, categoryselective patterns of response are still evident when images have been scrambled in a way that preserves some of their visual properties, but removes their semantic properties (Andrews et al, 2010;Coggan, Liu, Baker, & Andrews, 2016;Long, Yu, & Konkle, 2018;Watson, Andrews, & Hartley, 2017).…”
Section: Introductionmentioning
confidence: 99%